The Capital Structure of the Companies Quoted on the Warsaw Stock Exchange - Paweł Wnuczak (Contemporary Economics)
This paper presents the results of the research on the influence of capital structure on financial results of the companies quoted on the Warsaw Stock Exchange. The research shows a relation between a capital structure and a potential to increase firm value, return on equity and return on sales. The results of the research indicate how the companies quoted on the Warsaw Stock Exchange finances its assets and how it influences its financial standing.